MICROSCOPIC FEATURES OF CEMENT PASTE MODIFIED BY FINE PERLITE - Vladimír Hrbek; Veronika Koudelková; Pavel Padevět; Petr Šašek (Acta Polytechnica CTU Proceedings)
The use of waste material and replacement of binder element in cementitious composites is in focus of material development. Perlite in the construction industry is usually used in form of lightweight aggregate enhancing the insulating performance of concrete. This paper focuses on integration of fine perlite into the cement matrix and possible replacement of the cement binder in the composition of the material. The macromechanical performance of the modified paste is tested on specimens with 5, 10, 15 and 20% fine perlite substitution and pure cement sample. To distinguish the effect of the perlite on the microstructural level, pure cement material and specimen containing 10% of fine perlite are investigated by the electron microscopy. Furthermore, the mechanical properties of individual phases are examined and compared on same samples by instrumented indentation. The presented results enabled estimation of fine perlite impact on the macro and microscopic performance of the material.